Concepts and measures of patient empowerment: a comprehensive review - Paloma Garcimartín Cerezo; Maria-Euláli; Pilar Delgado-Hito
Abstract OBJECTIVE Analyze the definitions and dimensions of empowerment. Identify the strengths and weaknesses of empowerment measures based on the conceptual model. METHOD This was a comprehensive literature review of publications on the MEDLINE and Cumulative Index to Nursing and Allied Health Literature (CINAHL) databases. RESULTS Twenty-nine articles were selected. Seventeen definitions and seven dimensions of empowerment, and 10 empowerment measures were selected. Empowerment can be seen as an enabling process involving a shift in the balance of power, or as an outcome of this process. The dimensions reflect outcome indicators, such as participation in decision-making and control, and process indicators, such as knowledge acquisition and coping skills. Six of the tools analyzed by this study could be said to provide a robust measure of patient empowerment. CONCLUSION we propose a definition of empowerment that helps to deepen understanding of the term and, therefore, its operationalization.